Factors Associated with Extravasation Incident of Cancer Patients with Chemotherapy at RSUP Dr. Mohammad Hoesin Palembang - Atmajaya, Feri; Mat Sakar; Desti Elza Muslimah (RSUP Dr Moh Hoesin Palembang, 2022)
Cancer is currently the second leading cause of death in the world after heart disease. Global number of deaths from cancer in 2020 reached 10 million people. In Indonesia, the number of cancer sufferers has reached more than 369 thousand cases. Cancer treatment consists of various types such as intravenous chemotherapy. However, intravenous chemotherapy can cause complications at the injection spot known as extravasation. The incidence of extravasation at RSUP Dr Mohammad Hoesin Palembang is quite high. In 2019 there were 11 extravasation incidents, in 2020 there were 4 incidents, in 2021 there were 17 incidents and in the period January to October 2022 there were 32 extravasation incidents. This study aimed to determine what factors are associated with the incidence of extravasation in cancer patients with chemotherapy at RSUP Dr. Mohammad Hoesin Palembang. The research design used was a cross sectional purposive sampling technique with a total sample of 78 outpatient chemotherapy (One Day Care). Data analysis was carried out using the Chi Square test (X2). Statistical test results showed that gender, age and type of medicine was not related to the incidence of extravasation, while the vein's spot where the IV catheter inserted was significantly associated with the incidence of extravasation with a p value 0.043. It can be concluded that the incidence of extravasation is related to the vein spot where the intravenous catheter is inserted.